The crisis in brazilian prisons: putting prison education in context (Research, Society and Development, 2021)
The brazilian prison system has been suffering from problems that drastically affect the re-socialization of prisoners. This study considered fundamental rights in the prison context, namely: health, food, hygiene and, especially, education. The study aims to contextualize education in prison through the crisis in Brazilian prisons. It had an exploratory and descriptive narrative review, with a quantitative and qualitative approach. Taking into account the data presented, it is possible to notice that overcrowding has been frequent, with the number of prisoners exceeding that of vacancies in the period from 2017 to 2020. Therefore, there is a neglect of constitutional rights in relation to prisoners through violation of all sorts. It is reiterated that the prisoners must serve their sentences as required by law, but their fundamental rights cannot be relativized, subjecting them to inhuman conditions. The insertion of those sentenced to an education modality is also a way of reducing the time served and, consequently, a way of mitigating the overcrowding of prisons. Education gives these subjects the opportunity to reevaluate their actions, exercising being and acting in society. Finally, allowing prisoners to be able to remit penalties through education is not enough for a proposal for social integration, as education cannot be understood only from this perspective. Therefore, it is really desired that these subjects can reassess their role in society, understanding that being and acting need to respect the space of the other, in the sense that their perspective should be rethought.